Manhaj al-‘Ilāj al-Rūḥiy li Mudmina al-Mukhaddirāt bi Ma’had Inābah Surabaya - Anisa Nabela (Universitas Darussalam Gontor, 2017)
Spiritual psychotherapy is a way or method to deal with diseases which is related to the spiritual. This method is used for the purpose of increasing faith and monotheism through murāqabah only to Allah SWT alone, in order to obtain compassion from Him. One of the institutions that apply this method is Pondok Inabah Surabaya. In this Pondok Inabah, the application of therapy by healing the victims of drug addicts through psychological methods based on norms, rules and values in Islam, based on the Qur'an and Sunnah. Spiritual therapy at Pondok Inabah also applies the Sufi order method. In some cases a medical approach is also used. The method of spiritual therapy applied in Pondok Inabah Surabaya is all spiritual or spiritual activities using the method of the Qadaryah Naqsabandiyah Order which is central in spiritual therapy of students, such as: dzikr khāfī and dzikr jahr, ṣalāt, bath repentance, and kafarãt fasting. The time required in spiritual therapy is six months. Within six months, the students have to do a lot of spiritual activities, so the guidance on their mental health can be well controlled. To achieve mental health, they are required to set intentions seriously, beginning with repentance, submitting to God, and improving morals. Thus, there will be a love for God, so they can forget their dependence on drugs.